2007
DOI: 10.1021/bp070100+
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Induction Starting Time and Ca2+ on Expression of Active Penicillin G Acylase in Escherichia coli

Abstract: Formation of inclusion bodies is an important obstacle to the production of active recombinant protein in Escherichia coli. Thus, soluble expression of penicillin G acylase from Kluyvera citrophila was investigated in BL21(DE3). In this study, the yield of active enzyme was significantly enhanced by the composition of the medium and induction opportunity. When 0.5 mmol/L IPTG was added to complex medium at 15 h after incubation, the volumetric and specific activities of penicillin G acylase both achieved the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Regarding the auto-proteolytic processing of PAC, we observed that the size of both α- and β-subunits matched those of PAC obtained from Tth cells, suggesting a correct maturation of the pro-protein. Calcium proved to be a critical factor when producing functional Tth PAC, in the same way it was reported for the Eco PGA and Afae PGA [32,33]. The yield in active Tth PAC could be increased 13-fold when culture media was supplemented with 10 mM of CaCl 2 .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Regarding the auto-proteolytic processing of PAC, we observed that the size of both α- and β-subunits matched those of PAC obtained from Tth cells, suggesting a correct maturation of the pro-protein. Calcium proved to be a critical factor when producing functional Tth PAC, in the same way it was reported for the Eco PGA and Afae PGA [32,33]. The yield in active Tth PAC could be increased 13-fold when culture media was supplemented with 10 mM of CaCl 2 .…”
Section: Resultssupporting
confidence: 69%
“…Calcium ions have been suggested to stabilize the PGA native state allowing its maturation to take place [30,31]. Indeed, the production of properly matured PGA proteins in E. coli cells has been improved in cultures supplemented with CaCl 2 [32,33]. Hence, the influence of Ca +2 ions on the expression and maturation of Tth PAC was tested.…”
Section: Resultsmentioning
confidence: 99%
“…The augmentation of translation can be done by increasing the stability of pac mRNA, modifying the region of ribosome binding site, etc., leading to a mature PGA giving higher levels of activity [ 15 , 51 ]. The pac genes from bacterial strains other than E. coli have also been heterologously expressed in E. coli like genes from Arthrobacter viscosus [ 52 ], B. megaterium [ 53 ], Achromobacter xylosoxidans [ 54 ], P. rettgeri [ 55 ], A. faecalis [ 56 ], K. cryocrescens [ 57 ], and Thermus thermophilus [ 43 ]. Their PGAs can surpass EcPGA when expressed in E. coli in terms of particular enzymatic properties like wide operation range, molecular stability, and environmental tolerance [ 2 ].…”
Section: Main Textmentioning
confidence: 99%
“…This approach allows to increase the portion of the periplasmic enzyme nearly 100-fold, relative to the intracellular enzyme. High enzyme yields were also achieved using the richest medium, YE, of all those studied (YE, TH, MR, M9), as described in [60]. …”
Section: Expression Of Recombinant Pas In Ecolimentioning
confidence: 99%
“…Ca 2+ is important both for cellular growth [61] and for the formation of active soluble PA, since calcium ions are present in molecules of active PA [24,60]. According to some authors, Ca 2+ plays an important role in the translocation of the protein precursor across the membrane, as well as in the correct folding and maturation of the enzyme in the periplasm [31].…”
Section: Expression Of Recombinant Pas In Ecolimentioning
confidence: 99%